Identity Development: Analyzing the Professional Identity of After-school Tutors in China's Competitive Private Education Sector - Huang, Rui; Intarasompun, Wichian; Punchatree, Nuttamon (Journal of Advances in Humanities Research, 2023)
After-school tutoring has grown rapidly in China, employing millions of tutors. However, little research explores these tutors' professional identity development. This study aims to understand the factors shaping tutors' professional identity in Nanning's private tutoring sector. In-depth semi-structured interviews were conducted with 10 experienced tutors in Nanning selected through purposive sampling. The interview questions explored four dimensions of professional identity and influencing factors. Transcripts were analyzed using qualitative coding techniques. Major Findings show that Tutors' professional identity is shaped by their values, academic background, relationships, and work context. Passion for teaching competes with business priorities. Role confusion and lack of belonging challenge identity. Clear expectations, training, and institutional support are needed. The study concludes that by analyzing tutors' identity formation, this study provides insights into strengthening the tutoring profession. Regular training programs, positive student-tutor relationships, and a supportive work environment can enhance tutors' professional identity. Findings inform policies on tutor development in China's expanding private tutoring industry.